Imidacloprid Sorption and Transport in Cropland, Grass Buffer, and Riparian Buffer Soils. Issue 1 (12th April 2018) - Satkowski, Laura E.; Goyne, Keith W.; Anderson, Stephen H.; Lerch, Robert N.; Webb, Elisabeth B.; Snow, Daniel D.
Abstract : Core Ideas: Vegetative buffer strip (VBS) soils sorb imidacloprid (ICD) more than cropland soils due to greater SOC. Riparian VBS soils retard ICD leaching more than cropland and grass VBS soils. Results indicate ICD sorption to two or three sites, likely through different mechanisms. A VBS may reduce the mobility of ICD in agroecosystems. An understanding of neonicotinoid sorption and transport in soil is critical for determining and mitigating environmental risk associated with the most widely used class of insecticides. The objective of this study was to evaluate mobility and transport of the neonicotinoid imidacloprid (ICD) in soils collected from cropland, grass vegetative buffer strip (VBS), and riparian VBS soils. Soils were collected at six randomly chosen sites within grids that encompassed all three land uses. Single‐point equilibrium batch sorption experiments were conducted using radio‐labeled ( 14 C) ICD to determine solid–solution partition coefficients ( K d ). Column experiments were conducted using soils collected from the three vegetation treatments at one site by packing soil into glass columns. Water flow was characterized by applying Br − as a nonreactive tracer. A single pulse of 14 C‐ICD was then applied, and ICD leaching was monitored for up to 45 d. Bromide and ICD breakthrough curves for each column were simulated using CXTFIT and HYDRUS‐1D models. Sorption results indicated that ICD sorbs more strongly to riparian VBS ( K d = 22.6 L kg −1 ) than crop ( K d = 11.3 L kg −1 ) soils. Soil organic C was the strongest predictor of ICD sorption ( p < 0.0001). The column transport study found mean peak concentrations of ICD at 5.83, 10.84, and 23.8 pore volumes for crop, grass VBS, and riparian VBS soils, respectively. HYDRUS‐1D results indicated that the two‐site, one‐rate linear reversible model best described results of the breakthrough curves, indicating the complexity of ICD sorption and demonstrating its mobility in soil. Greater sorption and longer retention by the grass and riparian VBS soils than the cropland soil suggests that VBS may be a viable means to mitigate ICD loss from agroecosystems, thereby preventing ICD transport into surface water, groundwater, or drinking water resources.